THE EFFECTS OF PODCASTING ON EXAM PREPARATION AND ACADEMIC PERFORMANCE - Bajaj, Shivee; Rana, Pooja; Sharma, Trishu (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The swift integration of technology in education, propelled by the COVID-19 pandemic, has resulted in inventive methods of learning. Podcasting has become a valuable tool for enriching students' learning experiences. This study investigates the role of podcasting in exam preparation and its impact on academic performance among college students in Delhi NCR. This study investigates the influence of podcasting on the exam preparation and academic performance of university students. This research aims to provide evidence on the effectiveness of podcasts as a study tool by comparing the study habits and exam results of students who use podcasts with those who rely on traditional methods. Employing a mixed-methods approach, the study examines and contrasts two groups of students: one group utilizes podcasts for exam preparation while the other group relies on traditional study methods. The data collected from surveys, interviews, and exam scores offers valuable insights into the effectiveness of podcasting as a study tool. Based on extensive research, it has been found that podcasts have a significant positive impact on academic performance, student engagement, and the retention of course material. The study provides valuable insights for educators and policymakers to enhance exam preparation strategies through the use of podcasts.